Opening an onconephrology clinic: recommendations and basic requirements. Issue 9 (5th July 2018) - Cosmai, Laura; Porta, Camillo; Perazella, Mark A; Launay-Vacher, Vincent; Rosner, Mitchell H; Jhaveri, Kenar D; Floris, Matteo; Pani, Antonello; Teuma, Cécile; Szczylik, Cèzary A; Gallieni, Maurizio
Abstract: Onconephrology is a rapidly evolving subspeciality that covers all areas of renal involvement in cancer patients. The complexity of the field may benefit from well-defined multidisciplinary management administered by a dedicated team. Since there is an increasing need to address the needs of this population in dedicated outpatient clinics, it is critical to highlight basic characteristics and to suggest areas of development. In this brief perspective article, we analyse the requirements of an onconephrology clinic in terms of logistics, critical mass of patients and building a multidisciplinary team. We will further discuss which patients to refer and which conditions to treat. The last part of the article is dedicated to education and performance indicators and to analysis of the potential advantages of applying the hub-and-spoke model to this field. The ultimate aim of this experience-based article is to initiate debate about what an onconephrology outpatient clinic might look like in order to ensure the highest quality of care for this growing population of patients.